Improving Human Development Index (HDI) by Illiteracy Eradication (Case Study in Cibadak Village) - Indri Arrafi Juliannisa; Tri Siswantini (Jurnal Samudra Ekonomi dan Bisnis, 2020)
To measure the quality of human capital, The United Nations Development Program (UNDP) introduced the concept of human resource capital quality, named the Human Development Index (HDI). HDI is based on three dimensions i.e.: life expectancy at birth, literacy rate, mean years of schooling, and purchasing power parity. In this study raised the issue of the high illiteracy rate in Cibadak, Banten Province and the low expectation for old school. The situation will certainly be a barrier to the development process and economic growth through the human development index. The results showed that factors that could cause low educational status and illiteracy were grouped by researchers in research indicator variables, namely education, family, external environment, and information factors. The local government must pay more attention to this situation, because human resources are the driving wheel of the economy. The people really need care like reading and writing training assistance from the local government.